Adjuvant nutritional support for patients with acute-on-chronic liver failure reduce the risk of clinical complications - Ma, Wenjing; Qiu, Guoyuan; Liu, Hong (Frontiers in Nutrition, 2026)
BackgroundAcute-on-chronic liver failure (ACLF) patients face high risks of nutritional risk and clinical complications, but whether adjuvant nutritional support reduces adverse complications remains unclear.MethodsThis study included 6,097 hospitalized ACLF patients at West China Hospital. The Nutrition Risk Screening (NRS 2002) was used to assess the nutritional risk of the patients. Additional personalized enteral or parenteral nutrition was provided. The Kruskal–Wallis test and chi-square test compared continuous and categorical variables. Multivariate logistic regression analyzed odds ratios (ORs) and 95% confidence intervals (95% CI) for nutritional intervention and adverse outcomes, while the Cox model evaluated all-cause mortality risk.ResultsAmong participants (median age 53 years, 69.2% male), 52.5% (3,201) had nutritional risk, who were older, had lower body mass index (BMI), longer hospital stays, and higher rates of infection, hepatorenal syndrome, hepatic encephalopathy, coagulation disorders, and mortality (p < 0.01). After confounding adjustment, nutritional intervention in high-risk patients was associated with lower frequency of ascites (OR = 0.50, 95% CI: 0.31–0.80), infection (OR = 0.70, 95% CI: 0.52–0.94), and spontaneous bacterial peritonitis (SBP) (OR = 0.34, 95% CI: 0.24–0.49). Moreover, for patients without nutritional risk, nutritional intervention was also associated with lower frequency of ascites [0.26 (0.12–0.55)], SBP [0.30 (0.17–0.54)], and coagulation disorder [0.35 (0.17–0.72)]. Subgroup analysis showed consistent conclusions in most subgroups. However, nutritional intervention had no significant effect on improving all-cause mortality.ConclusionOver half of liver failure patients have nutritional risk. Adjuvant nutritional support was associated with significantly lower frequencies of clinical complications, especially ascites and SBP, regardless of nutritional risk.